5000 meter run performance is not enhanced 24 Hrs after an intense exercise bout and cold water immersion - Stenson, M. C.; Stenson, M. R.; Matthews, T. D.; Paolone, V. J. (Journal of Sports Science & Medicine, 2017)
Cold water immersion (CWI) is used by endurance athletes to speed recovery between exercise bouts, but little evidence is available on the effects of CWI on subsequent endurance performance. The purpose of this study was to investigate the effects of CWI following an acute bout of interval training on 5000 m run performance 24 hrs after interval training, perceived muscle soreness (PMS), range of motion (ROM), thigh circumference (TC), and perceived exertion (RPE). Nine endurance-trained males completed 2 trials, each consisting of an interval training session of 8 repetitions of 1200 m at a running pace equal to 75% of VO2peak, either a control or CWI treatment, and a timed 5000 m run 24 hrs post interval training session. CWI was performed for 12 min at 12 degrees Celsius on the legs. Recovery treatments were performed in a counterbalanced design. Run time for 5000 m was not different between the CWI and control trials (CWI = 1317.33 ± 128.33 sec, control = 1303.44 ± 105.53 sec; p = 0.48). PMS increased significantly from baseline to immediately post exercise (BL = 1.17 ± 0.22, POST = 2.81 ± 0.52; p = 0.02) and remained elevated from baseline to 24 hrs post exercise (POST24 = 2.19 ± 0.32; p = 0.02), but no difference was observed between the treatments. No differences were observed for the interaction between time and treatment for TC (Lambda = 0.73, p = 0.15) and ROM (Lambda = 0.49; p = 0.10). CWI performed immediately following an interval training exercise bout did not enhance subsequent 5000 m run performance or reduce PMS. CWI may not provide a recovery or performance advantage when athletes are accustomed to the demands of the prior exercise bout. Key Points: